Formation of Adolescents’ Understanding of Stunting Through The Communication Skilled Program at Vocational Schools - Stellarosa, Yolanda; Chrisdina, Chrisdina; Wempi, Jefri Audi; Septiana, Rizka (Institut Komunikasi dan Bisnis LSPR, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time resulting, in impaired growth in children. The Bandung Regency area is one of the areas experiencing an increasing number of stunting in years. Adolescents who are assumed to be the main element who should understand stunting, are not yet proven to be strong. A unique way is needed and should not give them the impression of being forced to learn new things. Communication and socialization training related to stunting issues is a strategy to instill an understanding of the importance of a healthy lifestyle as stunting prevention, as well as provide provisions to be able to disseminate this information through various innovations that can make their peers interested in stunting issues. This study used a quantitative research method, by distributing questionnaires to students at SMK Bintara Rancaekek, Linggar Village, West Java. The results of the study show that most respondents have a good understanding of stunting, which includes characteristics, causes, prevention, and participation or role, that adolescents want to carry out as agents of change in stunting prevention. Based on the results of the research, the provision included in communication training materials can be an alternative way of educating youth in the village. Keywords: Stunting, Adolescent Understanding, Communication Training, Agent of Change